Genome-wide DNA methylation analysis identifies kidney epigenetic dysregulation in a cystinosis mouse model - Rossi, M. N.; Ciolfi, A.; Matteo, V.; Pedace, L.; Nardini, C.; Loricchio, E.; Caiello, I.; Bellomo, F.; Taranta, A.; De Leo, E.; Tartaglia, M.; Emma, F.; et al. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionNephropathic cystinosis is a rare genetic disorder characterized by cystine accumulation in lysosomes that causes early renal dysfunction and progressive chronic kidney disease. Although several metabolic pathways, including oxidative stress and inflammation, have been implicated in the progression of renal parenchyma damage, the precise mechanisms driving its progression are not fully understood. Recent studies suggest that epigenetic modifications, particularly DNA methylation (DNAm), play a critical role in the development of chronic kidney disease. We hypothesized that epigenetic dysregulation may contribute to the progression of kidney disease in cystinosis.MethodsTo investigate this, we conducted genome-wide DNAm analyses on kidneys harvested from 6-month-old wild type (WT) and Ctns−/− mice, a well-established model of cystinosis.ResultsOur analysis revealed extensive DNAm alterations in cystinotic kidneys, characterized by a significant hypermethylation profile. Interestingly, the majority of differentially methylated CpG sites were located within gene bodies and to a lesser extent in promoter and enhancer regions. Methylation changes were primarily found in genes and pathways crucial for kidney function, particularly those related to the physiology of the proximal tubules. Importantly, DNAm changes correlated with changes in gene expression, as validated by qPCR analyses of key genes. Furthermore, in vitro treatment of human proximal tubular epithelial cells with the demethylating agent decitabine resulted in the upregulation of critical transporter genes, suggesting a potential therapeutic approach.ConclusionsThese findings underscore the role of epigenetic regulation in the progression of kidney damage in cystinosis and suggest that DNAm could serve as a promising target for novel therapeutic strategies.